A NOVEL CHRONOTHERAPEUTIC SYSTEM OF ETORICOXIB FOR TIME SPECIFIC DELIVERY BY MICROSPHERES AND TABLET LOADED CAPSULE SYSTEM - VR Teja Sruthi Pagadala; M.Lakshmi Surekha (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
The aim of this study was to create an innovative delivery system for Etoricoxib (ET) that offers dual pulse release as a therapeutic approach for rheumatoid arthritis. This system involves the use of microspheres and a tablet-in-capsule arrangement (MT-C).The design of this system involves an impermeable hard gelatin capsule body, inside which a core tablet (the second pulse) is placed at the bottom and sealed with a hydrogel plug (HP). The capsule body is then locked with an enteric-coated cap filled with KT microspheres (the first pulse). The selection of microspheres for the first pulse involved screening different formulations, and ET-M1 was chosen due to its small particle size and high drug loading.The criteria for selecting the second pulse (CT-2) included a disintegration time of 94 seconds and a cumulative drug release (CDR) of 95.56±0.37%. The formulation that met these criteria and achieved the maximum CDR by the end of 6 hours was considered the best.The hydrogel plug (HP) tablet was chosen based on its ability to maintain a lag period of 6 hours. The optimized formulations were then assembled according to the proposed design to create the pulsatile MT-C system, which was evaluated for in vitro release.The MT-C system demonstrated a delayed sustained CDR of 96.25% by the end of 10 hours from the first pulse (microspheres) after a 2-hour lag time. This was followed by a rapid release of ET from the second pulse (core tablet) in simulated colonic fluid within 10 hours.In conclusion, the in vitro pulsatile release system achieved a rational combination of delayed sustained and immediate release of ET. This system has the potential to address pain during the night and morning stiffness associated with rheumatoid arthritis. Incorporating two pulses into one system offers the advantage of reducing the frequency of dosing and improving pain management.